Maturity of Employment Data Interoperability in supporting One Employment Data at the Ministry and Regional Government Level - Herpita Wahyuni; Dyah Mutiarin; Wahyudi Kumorotomo; Ulung Pribadi; Nur Syakiran Akmal Ismail (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2023)
This research aims to determine the level of readiness or maturity of Employment Data Interoperability in supporting One Employment Data at the Ministry and Regional Government Level. Analyzing the maturity level of E-government interoperability across organizations in the Central Government and Regional Government in the Management of One Employment Data, namely: Preparedness, Understanding, Command Style and Ethos. This type of research is a type of mix method between critical discourse analysis. The research results show that the Preparedness indicator with a percentage of NVivo 12 Plus analysis results is 20.00% with the implementation of strengthening the implementation of one employment data policy by coordinating between central and regional employment agencies which aims to unify perceptions between the Ministry of Manpower and the Department in charge of employment regarding data standards, metadata, and employment data reference codes. Understanding with a percentage of 27.00% is well implemented and can provide implementation references and guidelines for central and regional agencies in order to realize the availability of quality, easily accessible and shared Employment Data between central and regional agencies. Command style (24.00%) is committed to building coordination and consolidation in order to achieve data interoperability. Ethos (27.00%) by carrying out the revitalization of One Employment Data's network and data security devices and hashtags in the data interoperability process which indicates that information related to work, training and the labor market can be better integrated for analysis and decision making purposes which is more effective.